North-Arctic Specificity of the Subject of Economic Research (Methodological Aspects) - Vitaliy N. Lazhentsev (Арктика и Север)
The North-Arctic topic of economic research covers a wide range of issues. The author believes that if we look at this topic from the standpoint of the methodology of constructing the subject of research, we cannot help but notice the growing importance of the axiological and evaluative aspects of studying the North. This kind of priority is conditioned by the increasing influence of natural conditions on socio-economic activity and the need for scientific explanation of transitions from natural to social. The methodology of practical activity in the conditions of the North traditionally reflects the difficulties of choosing the ways of organizing production and social activity here. At present, this is supplemented by the ambiguity of the reaction of the northern regions to the emergence of new circumstances that significantly affect the national economy, such as the need to urgently ensure the technological sovereignty of our country and strengthen its military-industrial complex. Therefore, the method of mobilization management becomes very relevant for the North of Russia, and especially for its Arctic zone. The scientific and practical aspects of the methodology of North-Arctic activities have a common methodological attitude: the transition from the position “the more the better” to the position “good quality is more important than large quantity”. Moreover, in the Arctic, the need for a transition “from the maximum necessary to the realistically possible” is increasingly realized.